The ER mitochondria calcium cycle and ER stress response as therapeutic targets in amyotrophic lateral sclerosis - Tadic, Vedrana; Prell, Tino; Lautenschlaeger, Janin; Grosskreutz, Julian (Frontiers in Cellular Neuroscience, 2014)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease characterized by progressive loss of upper and lower motor neurons. Although the etiology remains unclear, disturbances in calcium homoeostasis and protein folding are essential features of neurodegeneration in this disorder. Here, we review recent research findings on the interaction between endoplasmic reticulum (ER) and mitochondria, and its effect on calcium signaling and oxidative stress. We further provide insights into studies, providing evidence that structures of the ER mitochondria calcium cycle serve as a promising targets for therapeutic approaches for treatment of ALS.